Comparison of e‐cigarette use characteristics between exclusive e‐cigarette users and dual e‐cigarette and conventional cigarette users: an on‐line survey in France. (1st September 2019) - Berlin, Ivan; Nalpas, Bertrand; Targhetta, Rémi; Perney, Pascal
Abstract: Background and Aims: Completely substituting e‐cigarettes (EC) for combustible tobacco cigarettes reduces exposure to toxicants and carcinogens. However, a large proportion of EC users (dual users) continue to smoke conventional cigarettes. This study aimed to compare estimated nicotine intake and e‐cigarette use characteristics between exclusive EC users and dual users. Design: Web‐based anonymous cross‐sectional survey. Setting: France. Participants: A total of 3189 adults, current users of electronic cigarettes (EC). Data collection between 4 October 2014 and 11 November 2014. Measurements: Primary outcome: estimated nicotine intake per day (mg) from participants' reports. Secondary outcomes: duration, frequency of EC use and nicotine content of e‐liquids used/day. Dual use was defined as using at least one cigarette per day while also using EC. Findings: A total of 2836 respondents reported exclusive EC use and 353 reported being dual users. Backward stepwise logistic regression showed that dual users had higher estimated combined daily nicotine intake from e‐liquids and cigarettes [estimate: 2.14, standard error (SE) = 0.26, adjusted odds ratio (aOR) = 8.48, 95% confidence interval (CI) = 5.11–14.09, P < 0.001], but lower daily nicotine intake from EC (estimate: –2.14, SE = 0.26, aOR = 0.12, CI = 0.07–0.196, P < 0.001) and reported fewer months of EC use (estimate: −0.31, SE = 0.14, aOR = 0.73, CI = 0.56–0.95, P = 0.022) compared with exclusive EC users. Conclusion: Dual e‐cigarette users in France may have higher nicotine intake overall than exclusive e‐cigarette users, but they may take in less nicotine from their e‐cigarettes.